A NEGLECTED CONCEPT RELATED TO BUSINESSES: WORKPLACE BOREDOM PROBLEM - Taşar, Sezin Açık; Demir, Özcan (Fırat University, 2022)
Workplace boredom is one of the major problems facing businesses today. An employee who is physically in workplace but unable to use his/her full potential due to boredom problem, experiences loss of motivation, loss of working enthusiasm in that workplace and this can have negative consequences that can be costly for the businesses. Potential health problems, increase in intention of quitting from job, increase in the stress level and inefficiency are among the negative consequences of workplace boredom. For these reasons, the problem of boredom is a negative situation that renders the employee ineffective and pushes her to work below his/her capacity. In this study, a general informing about workplace boredom problem was made, the typology of the boredom experience was explained. In the following parts of the study, factors that caused the workplace boredom problem were mentioned. According to the important studies conducted on the subject in the literature, it has been observed that the most prominent cause of boredom problem is that the assignments given to the employee does not force the employee enough. On the other hand, another detail included in the study is the research in which the professions of law and project management, which are considered as the occupational group in which the employees have the most boredom problems, were determined. Moreover, in the study, the strategies in order to cope with this problem were stated. A related literature study was compiled. In the last part of the study, the suggestions of the managers and employees about the boredom problem were presented. This study contributes to the literature on employee well-being by extending the current knowledge on workplace boredom.

İşyerinde can sıkıntısı günümüzde işletmelerin yüzleştiği büyük problemlerin başında gelmektedir. İşyerinde can sıkıntısı sorunu sebebiyle fiziksel olarak işyerinde bulunduğu halde sahip olduğu tüm potansiyelini kullanamayan bir çalışan motivasyon kaybı yaşar, o işyerinde çalışma hevesini kaybeder ve bu da işletmeler için önemli ölçüde maliyetli olabilecek negatif sonuçlara sebebiyet verebilir. Oluşturacağı negatif sonuçlara örnek olarak çalışanın yaşayabileceği sağlık sorunları, çalışanın işten ayrılma niyetinin artması, stres seviyesinin artması ve çalışanın yaptığı işte verimsizlik yaşaması sayılabilir. Bu sebeplerden dolayı, can sıkıntısı problemi çalışanı etkisiz kılan ve sahip olduğu kapasitenin altında çalışmaya iten olumsuz bir durumdur. Bu çalışmada, işyerinde can sıkıntısı sorunun konusuyla alakalı genel bilgilendirme yapılmış, can sıkıntısı deneyiminin tipolojisi anlatılmıştır. Çalışmanın ilerleyen bölümlerinde ise can sıkıntısı sorununa neden olan faktörlerden bahsedilmiştir. Literatürde konuyla ilgili yürütülmüş önemli çalışmalara göre en göze çarpan can sıkıntısı problemi sebebi çalışana verilen sorumluluğun çalışanı yeterince zorlamaması sonucu oluştuğu gözlemlenmiştir. Öte yandan, çalışmada yer verilen bir diğer detay ise, çalışanlarının en çok can sıkıntısı problemi yaşadığı meslek grubu olarak değerlendirilen hukuk ve proje yönetimi mesleklerinin tespit edildiği araştırmadır. Ayrıca çalışmada, önemli negatif sonuçlara neden olabilecek can sıkıntısı problemi ile başa çıkma stratejilerine yer verilmiştir. Konuyla alakalı bir literatür çalışması da derlenmiştir. Çalışmanın son bölümünde ise, yöneticilerin ve çalışanların işyerinde can sıkıntısı sorunu konusunda çözüm önerileri sunulmuştur. Bu çalışma, iş yerinde can sıkıntısı problemi ile ilgili mevcut bilgileri genişleterek çalışan refahı konusunda literatüre katkı yapmaktadır.
İşletmelerin İhmal Ettiği Bir Kavram: İşyerinde Can Sıkıntısı Sorunu